Preparation and Performance of a P–N Containing Intumescent Flame Retardant Based on Hydrolyzed Starch. Issue 16 (2nd November 2017) - Qu, Hao; Fan, Ruilan; Yuan, Jianli; Liu, Bingbing; Sun, Lijie; Tian, Rongkai
ABSTRACT: Halogen-free flame retardant is receiving an increased attention recently due to its hypotoxicity and high efficiency. Intumescent flame retardant is a hot spot in research of the halogen-free flame retardant. In this work, a P–N containing intumescent flame retardant named hydrolyzed starch phosphamide from melamine was synthesized via hydrolysis of starch, phosphorylation of the starch with phosphorus oxychloride, and the reaction between the phosphorylated starch and melamine. PU/hydrolyzed starch phosphamide from melamine composites was prepared using different additive amounts of hydrolyzed starch phosphamide from melamine. Fourier transform infrared, scanning electron microscopy, and thermogravimetric analysis were used to characterize the structures and thermal stabilities of related compounds. Flame retardation performance of hydrolyzed starch phosphamide from melamine was investigated by UL94, limit oxygen index test, and cone calorimetry. Result shows that the PU/hydrolyzed starch phosphamide from melamine composites with 30.0 php of hydrolyzed starch phosphamide from melamine got a limit oxygen index of 29.0 and UL94-V0 ranking. Heat release rate, rate of smoke release, and total smoke release were decreased distinctly. GRAPHICAL ABSTRACT: